An Unusual Complication following Unconventional Use of High Pressure Injector. Issue 2 (March 2013) - Eroglu, SE; Tezel, S; Salcin, E; Denizbasi, A; Onur, O; Ozpolat, C; Demir, H
High pressure injection injuries most commonly occur in industrial accidents. In accident due to high pressure gun injuries, the nature of injected materials, the degree of toxicity, and the amount injected will affect the clinical outcome. Early vigorous treatment is essential to reduce morbidity. We reported a case of hand injuries due to inadvertent use of a high pressure injector device for haemostasis. 46-year-old male technician tried to stop bleeding from his injured hand by directing air jet from a high pressure injector to the wound resulting in significant subcutaneous emphysema. Adequate training and knowledge on occupational safety should be reinforced to avoid similar accidents.